Design and evaluation of a UV LED Photocatalytic Reactor Using Anodized TiO2 Nanotubes. (1st August 2016) - Ghosh, Jyoti P.; Achari, Gopal; Langford, Cooper H.
ABSTRACT: : A bench‐scale flow‐through photocatalytic reactor using light emitting diodes (LED) as light source and a TiO2 nanotube array (TN) as immobilized catalyst has been designed, fabricated and tested on commonly studied contaminants. The photoreactor is comprised of 144, 365‐nm UV‐LED lamps mounted along the inner periphery of an annular cylinder. An ordered array of TN, as catalyst, was immobilized by electrochemical anodization of a titanium cylinder and placed in the center of the reactor. Synthesized TN was characterized by scanning electron microscopy (SEM) and energy‐dispersive X‐ray spectroscopy (EDX). Laboratory investigations were conducted on the photoreactor to treat 4‐chlorophenol (4‐CP), atrazine and methylene blue. The performance of the photoreactor at different flow rates and at varying distances of photocatalyst from the light source was monitored. The photocatalytic reaction rates increased with bubbling oxygen into the reservoir. Significant improvement was observed when H2 O2 was added and degradation to detection limits was observed.